Human and novel coronavirus infections in children: a review. (2nd January 2021) - Rajapakse, Nipunie; Dixit, Devika
ABSTRACT: Coronaviruses, seven of which are known to infect humans, can cause a spectrum of clinical presentations ranging from asymptomatic infection to severe illness and death. Four human coronaviruses (hCoVs)—229E, HKU1, NL63 and OC43—circulate globally, commonly infect children and typically cause mild upper respiratory tract infections. Three novel coronaviruses of zoonotic origin have emerged during the past two decades: severe acute respiratory syndrome coronavirus (SARS-CoV-1), Middle East respiratory syndrome coronavirus (MERS-CoV) and the recently discovered severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which is the cause of the ongoing coronavirus disease 2019 (COVID-19) pandemic. These novel coronaviruses are known to cause severe illness and death predominantly in older adults and those with underlying comorbidities. Consistent with what has been observed during the outbreaks of SARS and MERS, children with COVID-19 are more likely to be asymptomatic or to have mild-to-moderate illness, with few deaths reported in children globally thus far. Clinical symptoms and laboratory and radiological abnormalities in children have been similar to those reported in adults but are generally less severe. A rare multisystem inflammatory syndrome in children (MIS-C) which has resulted in critical illness and some deaths has recently been described. Clinical trials for therapeutics and vaccine development should include paediatric considerations. Children may play an important role in the transmission of infection and outbreak dynamics and could be a key target population for effective measures to control outbreaks. The unintended consequences of the unprecedented scale and duration of pandemic control measures for children and families around the world should be carefully examined. Abbreviations: 2019-nCoV, 2019 novel coronavirus; ADEM, acute demyelinating encephalomyelitis; AAP, American Academy of Pediatrics; ACE-2, angiotensin-converting enzyme 2; ARDS, acute respiratory distress syndrome; BCG, bacillus Calmette–Guérin; BNP, brain natriuretic peptide; CDC, Centers for Disease Control and Prevention; CRP, C-reactive protein; CSF, cerebrospinal fluid; COVID-19, coronavirus disease 2019; CT, computed tomography; CXR, chest X-ray; DOL, day of life; hCoV, human coronavirus; ICU, intensive care unit; IL, interleukin; IVIG, intravenous immunoglobulin; KD, Kawasaki disease; LDH, lactate dehydrogenase; MERS, Middle East respiratory syndrome; MERS-CoV, Middle East respiratory syndrome coronavirus; MEURI, monitored emergency use of unregistered and experimental interventions; MIS-C, multi-system inflammatory syndrome in children; PCR, polymerase chain reaction; PICU, paediatric intensive care unit; RNA, ribonucleic acid; RCT, randomised-controlled trial; RSV, respiratory syncytial virus; SARS, severe acute respiratory syndrome; SARS-CoV-1, severe acute respiratory syndrome coronavirus 1; SARS-CoV-2, severe acute respiratory syndrome coronavirus 2; TNF-alpha, tumour necrosis factor alpha; UK United Kingdom; UNICEF, United Nations Children's Fund; USA, United States of America; WHO, World Health Organization